Teaching the wave concept through problem-based learning (2020)
The wave movements can be studied from autonomous work done by the student since they are processes in which he can appreciate and understand how the transmission of energy from one part to another without transfer of matter is. Problem-based learning constitutes a good alternative to study the concept of waves since it sequentially leads the student to structure the knowledge to use it in the context, to develop effective processes of reasoning, to develop self-directed learning skills and to motivate him/her to learn, together with the development of the capacity to work in a team and it favors the development of the mathematical physical thought. The research is developed from the multi-method methodological approach developing in-depth interviews to teachers and knowledge tests to students with the purpose of establishing both pre-knowledge and initial situations for structuring the pedagogical intervention and the evaluation of its results. The pedagogical intervention is structured on a quasi-experimental design in which the strategy of problem-based learning is applied to the teaching and learning of physics and is compared with the traditional methodology. The research allows us to conclude that applying the problem-based learning methodology to physics teaching, we obtain better educational yields than with traditional teaching, while it generates a greater motivation and a greater interest in learning. It also allows the student to integrate the knowledge into his or her context, visualize the usefulness of learning and apply knowledge to the solution of problems in his or her environment, in other words, it allows the student to achieve significant learning and therefore a development of mathematical physical thinking.